posted by Emmalene on .
Here is what I am trying to factor:
2x^2 + 3x + 1 = 0.
I split the middle term.
2x^2 + 3x - 1x + 1
Then grouped them.
(2x^2 +3x) + (-1x + 1)
Here is where I am having the problem. What should I do next?
Thank you! :-)
You did not split the middle term, you added a term "out of the blue".
The numbers to use to split the middle term are 2 and 1. When multiplied together, they give 2 (that is the product of a and c), and when added together they give 3 (that is b).
2x^2 + (2x + 1x) + 1 = 0
(2x^2 + 2x) + (1x + 1) = 0
pull out the GCF from each parentheses.
2x(x + 1) + 1(x + 1) = 0
not pull out the common factor (x + 1)
(x + 1)(2x + 1) = 0
see if you can take it from there.